ANALISIS TITIK PULANG POKOK USAHA BUDIDAYA LEBAH MADU âJAYA MAKMURâ DI DESA JONO OGE KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Anggraini, Ayu Dwi; Kassa, Saharia; Laapo, Alimudin (AGROTEKBIS, 2017)
The purposes of the research wereto determine the revenue, the expended cost, and the number of products at breaking event point, and to determine the margin of safety (MoS) for sustaining profit in honey bee âJaya Makmurâ farming of Jono Oge village, Sigi Biromaru sub district, Sigi district.Â  It was carried out in June to July 2015 with two respondent who was the owner and a worker of the farming.Â  The research showed that the revenue generated were IDR 2,860,000/month for a bottle of 850 ml honey with the production cost of IDR 1,684,267/month and the profit of 1,175,733/month; and IDR 3,055,000/month for a bottle of 400 ml honey with the production cost of IDR 1,699,130/month and the profit of 1,355,870/month.Â  The break event point achieved were 11bottles for the 850 ml product at the price of IDR 130,000/bottle and the sold price of IDR 1,495,000/month; and 23 bottles forÂ  the 400 ml product at the price of IDR 65,000/bottle and the sold price of IDR 1,430,00/month.Â  The MoS were 50% for the 850 ml product and 51% for the 400 ml product indicating that the maximum disparity limit for decreasing sale permitted for both products is not larger than the MoS ratio at the level of sale expected in July.Â Keywords: Analysis Of Â Break Event Point, Budidaya Lebah Madu, and Jono Oge Viilage,